1999
DOI: 10.1016/s0735-1097(99)00064-9
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of coenzyme Q on left ventricular function in patients with congestive heart failure11Coenzyme Q and matching placebo tablets were supplied by Health World Limited, Brisbane, Australia.

Abstract: In patients with left ventricular dysfunction, treatment for three months with oral coenzyme Q failed to improve resting left ventricular systolic function or quality of life despite an increase in plasma levels of coenzyme Q to more than twice basal values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The incremental benefit of ubiquinone over and above these agents would have produced the most interesting data. However three studies reported no benefit of ubiquinone on existing treatment of heart failure in subjects with low ejection fraction [ 35 , 36 , 37 ]. In one study atrial fibrillation was present and in two studies, the plasma levels of ubiquinone did not reach a desired level and both patients were suffering cardiomyopathy without AMI.…”
Section: Discussionmentioning
confidence: 99%
“…The incremental benefit of ubiquinone over and above these agents would have produced the most interesting data. However three studies reported no benefit of ubiquinone on existing treatment of heart failure in subjects with low ejection fraction [ 35 , 36 , 37 ]. In one study atrial fibrillation was present and in two studies, the plasma levels of ubiquinone did not reach a desired level and both patients were suffering cardiomyopathy without AMI.…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between coenzyme Q10 and the prevention of the risk of CAD are controversial. Some studies reported the plasma coenzyme Q10 concentration was not related to the risk of coronary atherosclerosis, and there was no beneficial effect of coenzyme Q10 in patients with CAD [9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 illustrates the distribution of size, design and follow-up length of the analyzed clinical studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%